Ethical concepts: duty-based theories. (2nd January 2020) - Ellis, Peter
Abstract : In previous articles, the theory of consequentialism and its pros and cons have been explored. Consequentialism is focused on the outcomes or consequences of any action undertaken and its ethicality. Here, Peter Ellis starts a discussion of duty-based ethics, where the rightness or wrongness of an action itself is considered.